Effect of teaching style on cognitive acquisition and development of some basic skills - نوري, ئاراز محمد (Sulaimani Journal for Humanities, 2019)
The objective of the study was to identify the effect of the learning technique on the development of some basic skills of handball and cognitive achievement. The experimental method was used in the two groups of tribal and post-test tests. (20) players as well as (6) players were randomly selected for the pilot experiment, and then exclude those players from the main experiment, thus the number of players in the experimental and control groups (20) players by (10) Playthings for each group, and then the two groups were selected (experimental and control) was applied to the educational units of the experimental group of (24) educational unit has been applied by three educational units per week, and the results were processed by statistical means appropriate. The researcher concluded the effect of the technique of learning proficiency remarkable in some of the basic skills of handball and cognitive achievement and this is illustrated by the differences between the tests of tribal and remote tests and the interest of remote tests.